2018
DOI: 10.1038/s41598-018-22857-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells protect against n-hexane-induced neuropathy through beclin 1-independent inhibition of autophagy

Abstract: Chronic exposure to n-hexane, a widely used organic solvent in industry, induces central-peripheral neuropathy, which is mediated by its active metabolite, 2,5-hexanedione (HD). We recently reported that transplantation of bone marrow-mesenchymal stem cells (BMSC) significantly ameliorated HD-induced neuronal damage and motor deficits in rats. However, the mechanisms remain unclear. Here, we reported that inhibition of HD-induced autophagy contributed to BMSC-afforded protection. BMSC transplantation significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Nevertheless, these cytokines (Dang et al, 2014) found that inflammatory condition hampered the immunoinhibitive potential of MSCs by priming autophagy in a mouse model of experimental autoimmune encephalitis, supporting our findings. Similar results indicating protective effect of bone MSCs on n-hexane-induced neuropathy through autophagy inhibition were also found in another study (Hao et al, 2018). Collectively, our results demonstrate that counteracting LF microenvironment-induced autophagy via stable knockdown of Becn1 remarkably promotes the antifibrotic effects of MSCs.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, these cytokines (Dang et al, 2014) found that inflammatory condition hampered the immunoinhibitive potential of MSCs by priming autophagy in a mouse model of experimental autoimmune encephalitis, supporting our findings. Similar results indicating protective effect of bone MSCs on n-hexane-induced neuropathy through autophagy inhibition were also found in another study (Hao et al, 2018). Collectively, our results demonstrate that counteracting LF microenvironment-induced autophagy via stable knockdown of Becn1 remarkably promotes the antifibrotic effects of MSCs.…”
supporting
confidence: 90%
“…Importantly, proinflammatory cytokines are a prerequisite for MSCs to exert their immuneinhibitory functions (Ren et al, 2008). Nevertheless, these cytokines n-hexane-induced neuropathy through autophagy inhibition were also found in another study (Hao et al, 2018). Collectively, our results demonstrate that counteracting LF microenvironment-induced autophagy via stable knockdown of Becn1 remarkably promotes the antifibrotic effects of MSCs.…”
Section: Autophagy Of Mscs Occurred In a Lf Microenvironmentmentioning
confidence: 53%
“…Motor neurons that originated from the Ventral sciatic nerve 4.1 (VSC4.1) [35,37,38] were produced and cultured. Briefly, embryonic motor neurons from the rat ventral sciatic nerve were fused with mouse neuroblastoma cells (N18TG2), which were grown at 37°C in poly-L−ornithine coated flasks in a 5% CO 2 incubation system.…”
Section: Methodsmentioning
confidence: 99%
“…Under the catalysis of E1-like enzyme ATG7 and E2-like enzyme ATG10, the formed ATG5/ATG12/ATG16(L) complex facilitates the recruitment and conversion of microtubule­associated protein light chain 3 (LC3-I) to the membrane-bound LC3-II form [ 11 ]. LC3-II also binds to the adaptor protein p62/sequestosome1 (SQSTM1) to degrade the ubiquitinated protein aggregates in autophagolysosome [ 12 ], and thus recycling amino acids and other metabolic building blocks to maintain cellular homeostasis.
Fig.
…”
Section: Mechanisms Of Autophagymentioning
confidence: 99%